Vitiligo et phénomène de Koebner suite à des injections de plasma riche en plaquettes - Ejjiyar, Mouna (Pan Afr Med J, 2019)
Vitiligo is a common and acquired skin pigmentation disorder characterized by a selective and often continuous loss of epidermal melanocytes. We report the case of a female patient who developed facial vitiligo following platelet-rich plasma injections. The diagnosis of Koebner phenomenon was retained in order to explain the occurrence of vitiligo on the areas where platelet-rich plasma (PRP) had been injected.